2021
DOI: 10.1101/2021.09.24.461726
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Express Arm Responses Appear Bilaterally on Upper-limb Muscles in an Arm Choice Reaching Task

Abstract: When required, humans can generate very short latency reaches towards a visual target, like catching a phone falling off a desk. During such rapid reaches, express arm responses are the first wave of upper limb muscle recruitment, occurring within ~80-100 ms of target appearance. There is accumulating evidence that express arm responses arise from signaling along the tecto-reticulo-spinal tract, but the involvement of the reticulo-spinal tract has not been well-studied. Since the reticulospinal tract projects … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 69 publications
(168 reference statements)
0
3
0
Order By: Relevance
“…In this context, it is also worth mentioning that our interelectrode spacing of 2.5 mm is much smaller than the typical distances used in many grid arrays and could have contributed to isolating a larger proportion of smaller motor units. Third, unlike many previous reports, our study focussed on proximal shoulder muscles that may be preferentially targeted by the reticulospinal system that may be responsible for the observed delayed activity since these muscles also robustly express a stimulus locked response (Kearsley et al 2021). Finally, since this early activity was correlated with RT, had spatially selective response fields (see Fig S5 ) and was only observed for delayed movements but not for cursor movements generated by isometric muscle force, it cannot be an artifact.…”
Section: Methodological Issuesmentioning
confidence: 94%
See 2 more Smart Citations
“…In this context, it is also worth mentioning that our interelectrode spacing of 2.5 mm is much smaller than the typical distances used in many grid arrays and could have contributed to isolating a larger proportion of smaller motor units. Third, unlike many previous reports, our study focussed on proximal shoulder muscles that may be preferentially targeted by the reticulospinal system that may be responsible for the observed delayed activity since these muscles also robustly express a stimulus locked response (Kearsley et al 2021). Finally, since this early activity was correlated with RT, had spatially selective response fields (see Fig S5 ) and was only observed for delayed movements but not for cursor movements generated by isometric muscle force, it cannot be an artifact.…”
Section: Methodological Issuesmentioning
confidence: 94%
“…However, despite the presence of gating mechanisms, certain behavioral paradigms that typically evoke reflexive activity have been shown to initiate early recruitment of proximal limb muscles in cats, monkeys, and humans (Fautrelle et al 2010;Perfiliev et al 2010;Saijo et al 2005;Schepens and Drew 2003). These studies also show that stimuluslinked activity can also be observed in shoulder muscles during such rapid reflexive movements (Kearsley et al 2021;Pruszynski et al 2010).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation